Transformasi Partisipasi dan Pengalaman Spiritual Penyembahan Gereja di Era Digital: Analisis Teologis Pemanfaatan Media Sosial - Rahayu, Meliska Putri; Arifianto, Yonatan Alex (MAWAR SARON: Jurnal Pendidikan Kristen dan Gereja, 2026)
Digital transformation has significantly altered worship practices within church life, particularly in the way congregants express their faith and participate in worship. Advances in communication technology have driven a shift from physical worship towards more flexible virtual spaces. These changes call for deep theological reflection to ensure that worship practices remain rooted in the essential principles of the Christian faith. The phenomenon of the increasing use of social media in church worship indicates that the digital space has become an integral part of the congregation’s spiritual life. Online worship through live streams, spiritual content, and digital interaction significantly expands the reach of the church’s ministry. However, this phenomenon also presents challenges in the form of distractions, a decline in the quality of engagement, and a tendency towards a consumerist approach to worship. The research findings indicate that digital worship retains its theological legitimacy as long as the relationship of faith, active participation, and orientation towards God are maintained. Furthermore, social media serves as a strategic tool for expanding ministry and building an inclusive community of faith. However, an adaptive pastoral approach is required to preserve the spiritual depth of the congregation. This study aims to analyse the transformation of participation and spiritual experience in digital worship practices from a theological perspective. The method employed is a qualitative approach through a literature review. In conclusion, digital transformation presents both opportunities and challenges for the church in maintaining a balance between innovation and the theological essence of worship. The church is called upon to develop strategies that are contextual and rooted in faith. Thus, digital worship can become an effective means for spiritual growth and the expansion of the church’s ministry.